Creating new dimension in marketing new destination in Jordan: suggested strategy for Aqaba region / Jamal Hussein El-Harami - El-Harami, Jamal Hussein (Universiti Teknologi MARA (UiTM), Malaysia, 2012)
The main goal of this research is to improve marketing of tourism destinations in Aqaba region by including the well-known archaeological site in Madain Saleh north western Saudi Arabia. Recently Aqaba region witnessed major developments in tourism infrastructure by the construction of luxury hotels and resorts undertaken by Tala Bay, Saraya, Ayla, Marsa Zayed projects with upon completion will transform Aqaba into an important tourist destination in the region. These giant tourist projects will definitely require serious and innovative venues of marketing able to generate large numbers of tourists from around the world. Aqaba is marketed with Wadi Rum and Petra as the golden triangle of tourism. By including Madain Saleh the sister city of Petra the name will be the golden quadrangle of tourism. Joint marketing the four destinations with the cooperation of Saudi Arabia tourism authority will open the door for citizens and residents from the Gulf States to travel and see deferent destination. Cruiseship tourism will also be considered.